Perception of food quality among Saudi consumers - Abdulrahman Alshuniaber, Mohammad (Italian Journal of Food Science, 2024)
Consumers’ perceptions of quality of food products increase their purchasing likelihood. This study provides a framework for exploring consumers’ perceptions of food quality for food product development and food marketing strategies by providing vital information related to consumer behavior and food choice. It establishes a method for measuring food quality perceptions through a validated questionnaire. It was found that adult consumers in Riyadh City, Saudi Arabia, perceive intrinsic food characteristics higher than of extrinsic food characteristics. Characteristics related to product safety, nutritional value, and sensory attributes were the most highly valued aspects. Sociodemographic factors such as age, marital status, education, occupation, income, and work/study in the food field were found to affect Saudi consumers’ perceptions of food quality. Furthermore, marital status, education, occupation, and income were the major classification factors for perception trends. Food identity and processing, food health prosperity, food safety and presentation, and food sensory attributes were the major qualities perceived by Saudi consumers.